Direct assessment of preferences for social interactions in children with autism. Issue 4 (14th August 2013) - Call, Nathan A.; Shillingsburg, M. Alice; Bowen, Crystal N.; Reavis, Andrea R.; Findley, Addie J.
<x xml:space="preserve">Abstract</x> Qualitative and quantitative differences in social interactions are core symptoms of the autism spectrum disorder (ASD) diagnostic criteria, although there is heterogeneity among individuals with ASDs. This study used a concurrent operants arrangement to evaluate whether social interactions functioned as positive reinforcement, negative reinforcement, or as neutral stimuli for 6 individuals with autism. Data suggest that clinicians who work with individuals with ASD should ascertain the functional properties of social interactions prior to using them as a consequence in interventions.